ANALISIS YURIDIS KEDUDUKAN STRATIFIKASI SOSIAL DALAM HUKUM DARI PERSPEKTIF TEORI FUNGSIONALISME STRUKTURAL - amelia lia (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
Humans as social beings need each other, the interactions that exist make them dependent on each other, this situation is what makes social groups in society form. Of course, the emergence of social groups creates gaps between them, this is what ultimately forms the social strata in society which is known as social stratification. The emergence of social strata forms discrimination between people who have high social class and people who have low social class (wealth, education, position, status, etc.). The social stratum that is formed eventually causes discrimination against the lower social class, the higher social class will be treated more favorably than the lower social class. The upper-class layer is still considered the educational personification of the structure. That is, it is the top layer that determines where the community is going. The top layer also determines the positive law that applies in society, then applies it to the layers below it. The role of the layers of society in law is the top layer as a structure, while the lower layer functions as a structural tool. This is where in fact the question of the position of social stratification in law from the point of view of the theory of structural functionalism.